A multidimensional strategy to managing dysfunctional breathing and exercise-induced laryngeal obstruction in adolescent athletes - Liv-Jorunn Kolnes; Trine Stensrud; Oddbjørn Klomsten Andersen (BMC, 2024)
Abstract Background Exercise induced laryngeal obstruction (EILO) causes inspiratory distress in the upper airway in many adolescent athletes. The nature of EILO is not fully understood, and effective management strategies are lacking. This study aimed to assess the effectiveness of a multidimensional individually tailored intervention, including Norwegian Psychomotor Physiotherapy (NPMP), elements of cognitive behavioural therapy and a rehabilitation plan, in reducing inspiratory distress and dysfunctional breathing in adolescent athletes with EILO. Methods A mixed methods design, which combined qualitative and quantitative research, was used. Data, including subjective experiences of respiratory distress, findings from body examinations and objective measurements of lung function and aerobic capacity were gathered before and after a five month intervention involving 18 participants. Results Following the intervention, the participants showed a reduction in respiratory distress and anxiousness associated with their breathing difficulties. Furthermore, the participants reported to be more in control of their breathing. The body assessments revealed a more functional breathing motion and improved posture, which imply that the breathing was less thoracic and more diaphragmatic in rest and exercise in all participants after the intervention. Conclusions Our results suggest that a multidimensional individually tailored intervention, including NPMP based physiotherapy, cognitive behavioural therapy elements, and a rehabilitation plan may reduce inspiratory distress and dysfunctional breathing in athletes with EILO. Trial registration ClinicalTrials.gov Protocol Registration and Results system NCT06033755, date of registration: September12, 2023. Retrospectively registered.